2021
DOI: 10.1039/d1tc02985a
|View full text |Cite
|
Sign up to set email alerts
|

An insight study into the parameters altering the emission of a covalent triazine framework

Abstract: Covalent triazine frameworks (CTFs) synthesized through nucleophilic substitution of 4,4’ bipyridine on the carbon atoms of cyanuric chloride were studied as fluorescent sensors. The band gap of the materials was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Furthermore, our group demonstrated that the bulk layered network could undergo an exfoliation process toward few-layered sheets or nanostructures through sonication in aqueous or tetrahydrofuran dispersions. 35 With respect to the well-known tendency of pyridine moieties to form coordination complexes with divalent copper, we examined the ability of the frameworks to absorb copper. The networks reacted immediately with copper ions, and an insoluble precipitate was immediately formed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, our group demonstrated that the bulk layered network could undergo an exfoliation process toward few-layered sheets or nanostructures through sonication in aqueous or tetrahydrofuran dispersions. 35 With respect to the well-known tendency of pyridine moieties to form coordination complexes with divalent copper, we examined the ability of the frameworks to absorb copper. The networks reacted immediately with copper ions, and an insoluble precipitate was immediately formed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Depending on the geometry of the central core, the network can grow in two or three dimensions. Furthermore, our group demonstrated that the bulk layered network could undergo an exfoliation process toward few-layered sheets or nanostructures through sonication in aqueous or tetrahydrofuran dispersions …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure, morphology, and chemical composition of the g-C 3 N 4 material and the bCOF have been previously described in references of Papailias et al [25] and Bika et al [32]. The FTIR spectra of the pristine and heterojunction materials with the three different ratios are presented in the order of (i) g-C 3 N 4 , (ii) HJ(1:10), (iii) HJ(1:1), (iv) HJ(10:1), and (v) bCOF, in Figure 1a (range: 500-2000 cm −1 ) and Figure S2 (range: 400-4000 cm −1 ).…”
Section: Chemical and Structural Characterisationmentioning
confidence: 99%